Childhood nutrition in Mexico: A diagnosis study of indigenous children of the Totonacapan - Valdes, Luis Roberto Canto; Cortés-Ruiz, Juan Antonio; Reyes, César; Cureño, Hebert Jair Barrales; Hernández, Edora Reyes (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
In this work was made a diagnostic analysis about the nutritional quality of indigenous children of the community of Huehuetla, State of Puebla, Mexico is known as Totonacapan. The study was performed in the children´s garden “Jardin de niños de Huehuetla” from 5 to 9th November 2015. In order to determine the nutritional quality in children from 3 to 5 years old was carried out anthropomorphic measurements through body mass index (BMI) and the amount of calorie ingested daily. The sample consists of 57 children, which were classified by age: 3, 4 and 5 years old. According to BMI, children of 3 years do not show symptoms of malnutrition; for children of four years old, only 7.1 % of female showed undernutrition signals. In the case of children of five years old, 30 % presented overweight and obesity (30 %). Totonaco children analyzed consumed between 800 to 1150 Kcal/day, indicating that there is not a direct relationship between daily calorie consumption against BMI. Finally, totonaco children have a low diet in fat, but rich in carbohydrates and 30 % of them could suffer some degree of malnutrition.                             The children sample analyzed in this study and in accord to anthropomorphic measurements, indicate that there is not apparent malnutrition on totonaco children between three and five years.